Muscle magnetic resonance imaging in congenital myasthenic syndromes. Issue 2 (22nd February 2016) - Finlayson, Sarah; Morrow, Jasper M.; Rodriguez Cruz, Pedro M.; Sinclair, Christopher D.J.; Fischmann, Arne; Thornton, John S.; Knight, Steve; Norbury, Ray; White, Mel; Al‐hajjar, Michal; Carboni, Nicola; Jayawant, Sandeep; et al.
ABSTRACT: Introduction: In this study we investigated muscle magnetic resonance imaging in congenital myasthenic syndromes (CMS). Methods: Twenty‐six patients with 9 CMS subtypes and 10 controls were imaged. T1‐weighted (T1w) and short‐tau inversion recovery (STIR) 3‐Tesla MRI images obtained at thigh and calf levels were scored for severity. Results: Overall mean the T1w score was increased in GFPT1 and DPAGT1 CMS. T1w scans of the AChR‐deficiency, COLQ, and CHAT subjects were indistinguishable from controls. STIR images from CMS patients did not differ significantly from those of controls. Mean T1w score correlated with age in the CMS cohort. Conclusions: MRI appearances ranged from normal to marked abnormality. T1w images seem to be especially abnormal in some CMS caused by mutations of proteins involved in the glycosylation pathway. A non‐selective pattern of fat infiltration or a normal‐appearing scan in the setting of significant clinical weakness should suggest CMS as a potential diagnosis. Muscle MRI could play a role in differentiating CMS subtypes. Muscle Nerve 54 : 211–219, 2016